Theoretical Justification of Optimal Geometric and Kinematic Parameters in the Moving Parts of Clod-Crusher for Potato Harvester - Tarverdyan, A. P.; Hayrapetyan, H. H. (ՀԱԱՀ հիմնադրամ)
The impact of geometric forms and sizes of the working parts in the automated clod crusher of the potato harvester on the soil-sticking and motion resistance force, as well as on the clods strike and their throwing velocity have been studied. Theoretic investigations have resulted in the derivation of expressions which enable to determine the resistance force and the clods throwing velocity for cylindrical flat-fronted, cylindrical hemispheric-fronted and conical headed clod crushers. It has been disclosed that the form of the crusher’s working part practically has zero impact on the soil clods throwing velocity; it is a constant value for all considered cases.
Keywords: Agricultural Engineering